2019
DOI: 10.4254/wjh.v11.i5.412
|View full text |Cite
|
Sign up to set email alerts
|

Roles of hepatic stellate cells in acute liver failure: From the perspective of inflammation and fibrosis

Abstract: Acute liver failure (ALF) usually results in hepatocellular dysfunction and coagulopathy and carries a high mortality rate. Hepatic stellate cells (HSCs) are famous for their role in liver fibrosis. Although some recent studies revealed that HSCs might participate in the pathogenesis of ALF, the accurate mechanism is still not fully understood. This review focuses on the recent advances in understanding the functions of HSCs in ALF and revealed both protective and promotive roles during the pathogenesis of ALF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…Studies have shown that liver injury caused by different factors has relatively specific inflammatory microenvironment characteristics 22,23 . We found that TNF-α was significantly increased in the livers of WT rats after LPS injection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that liver injury caused by different factors has relatively specific inflammatory microenvironment characteristics 22,23 . We found that TNF-α was significantly increased in the livers of WT rats after LPS injection.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, KCs can respond to exposure to LPS by binding to TLR4 which leads to production of inflammatory cytokines (TNF-α, IL-1β, IL-6, IL-12, IL-18, etc.) and other chemokines [72], most of them being actively involved in HSCs activation (Table 2) [5,[73][74][75]. Other macrophages recruited to the liver in the case of inflammation, are also involved in secretion of pro-and anti-inflammatory cytokines, depending on their type (proinflammatory M1 or immunosuppressive M2, respectively).…”
Section: Inflammatory Signals From Kupffer Cells and Other Inflammatimentioning
confidence: 99%
“…Its 1-year mortality ranges from 1% to 57% depending on the stage. To date, the only treatment of developed cirrhosis is liver transplantation [1].…”
Section: Introductionmentioning
confidence: 99%